Essays of E. B. White. - White, E. B. (Elwyn Brooks), 1899-1985. (New York : Harper & Row, 1977)
Thirty-one of E.B. White's essays grouped under such headings as "The Farm," "The Planet," "Memories," and "Books, Men, and Writing.".
School Library Journal.
Wilson's Public Library.
Wilson's Senior High School.
Young Adult.
Young Adult
Keywords: American essays; American essays